Inter-Religious Marriage: A Comparison Analysis of Indonesian Law With Other Countries - Tomi Hidayatullah; Oemar Moechthar; Dimipta Aprilia (Fakultas Hukum Universitas Airlangga, 2023)
AbstractInter-religious marriage is not something new in Indonesia. Judging from the diversity of religions that exist, it does not rule out the possibility of inter-religious marriages. However, inter-religious marriage is still a polemic among the public because the Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage, does not explicitly regulate and accommodate the problem of inter-religious marriage, especially after the enactment of Law Number 23 of 2006 concerning Administration Population, the opportunity to legalize inter-religious marriages seems to be wide open, namely with the availability of the option of submitting an application for interfaith marriages to the District Court to issue a stipulation allowing interfaith marriages and instructing Civil Registry office employees to record these interfaith marriages into Register of Marriage Registration. In the end, people often smuggle laws in ways that are not justified, for example by providing false information that they have changed religions and follow the religion of their partners. Or by carrying out marriages abroad which allow marriages of different religions, and then registering them at the civil registry office. This study aims to find out how Indonesian law views inter-religious marriages and how inter-religious marriages are regulated from a comparison of the laws of other countries, such as those in Canada, Singapore, England and the Netherlands. This study uses a statutory approach, namely an approach that is carried out by examining all laws and regulations that are related to the legal issues under study. The results of this study will provide input to Indonesian legislators which can be used as an improvement in regulations, especially provisions related to inter-religious marriage.Keywords: Interfaith Marriage; Reduced Inequalities; Comparative Civil Law; Peace and Justice.